The Microbiome of the Medicinal Plants Achillea millefolium L. and Hamamelis virginiana L. - Sauer, Simon; Dlugosch, Leon; Kammerer, Dietmar R.; Stintzing, Florian C.; Simon, Meinhard (Frontiers in Microbiology, 2021)
In the recent past many studies investigated the microbiome of plants including several medicinal plants (MP). Microbial communities of the associated soil, rhizosphere and the above-ground organs were included, but there is still limited information on their seasonal development, and in particular simultaneous investigations of different plant organs are lacking. Many studies predominantly addressed either the prokaryotic or fungal microbiome. A distinction of epi- and endophytic communities of above-ground plant organs has rarely been made. Therefore, we conducted a comprehensive investigation of the bacterial and fungal microbiome of the MP Achillea millefolium and studied the epi- and endophytic microbial communities of leaves, flower buds and flowers between spring and summer together with the microbiome of the associated soil at one location. Further, we assessed the core microbiome of Achillea from four different locations at distances up to 250 km in southern Germany and Switzerland. In addition, the bacterial and fungal epi- and endophytic leaf microbiome of the arborescent shrub Hamamelis virginiana and the associated soil was investigated at one location. The results show a generally decreasing diversity of both microbial communities from soil to flower of Achillea. The diversity of the bacterial and fungal endophytic leaf communities of Achillea increased from April to July, whereas that of the epiphytic leaf communities decreased. In contrast, the diversity of the fungal communities of both leaf compartments and that of epiphytic bacteria of Hamamelis increased over time indicating plant-specific differences in the temporal development of microbial communities. Both MPs exhibited distinct microbial communities with plant-specific but also common taxa. The core taxa of Achillea constituted a lower fraction of the total number of taxa than of the total abundance of taxa. The results of our study provide a basis to link interactions of the microbiome with their host plant in relation to the production of bioactive compounds.